-2-3x=6+10

Simple and best practice solution for -2-3x=6+10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2-3x=6+10 equation:


Simplifying
-2 + -3x = 6 + 10

Combine like terms: 6 + 10 = 16
-2 + -3x = 16

Solving
-2 + -3x = 16

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2' to each side of the equation.
-2 + 2 + -3x = 16 + 2

Combine like terms: -2 + 2 = 0
0 + -3x = 16 + 2
-3x = 16 + 2

Combine like terms: 16 + 2 = 18
-3x = 18

Divide each side by '-3'.
x = -6

Simplifying
x = -6

See similar equations:

| -2-3x=2+10 | | -2-3x=3+10 | | (0.72*1.2x)+(0.28*x)=8 | | (0.72*1.2x)+(0.28*x)=4.5 | | x=y^(1/5) | | 49x^3+x=0 | | 13.2=2*pi*r | | t^2-12t-28=0 | | 91+3b=37-3b | | 37-4x=77+6x | | x*x+x*y+x*y=0.64 | | |5x-1|/|x-2|=4 | | (4s+2)(5s^2+10s+3)= | | (0.7*1.5x)+(0.3*x)=4.5 | | 71+n=100 | | 3(2b+5a)= | | 3c+45=3-4c | | 1,3/16 | | (0.5*1.2x)+(0.5*x)=16 | | z^2-5=-7 | | z^2=-6 | | (0.5*1.2x)+(0.5*x)=8 | | (8)3/4×(4096)1/2÷1/(64)= | | 4y-5=7y-20 | | 13p+14q+p-6q-5p= | | X+3y+26whenx=2whatisy | | logb^8=-3 | | (0.61*1.2x)+(0.39*x)=6 | | 1120=(x+3)(x+4)(5+x)(6+x)(7+x) | | (3x^y^4-11xy^4)/55xy | | 23=m-19 | | 8x+18=3x-2 |

Equations solver categories